SECURE AUTHENTICATION SCHEMES: METHODS AND SECURITY ANALYSIS - Kapalova, Н.А.; Yergesh, Н.С. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2026)
This paper systematizes key methods for designing secure authentication schemes in information systems and provides a combined theoretical and practical analysis of their security properties. The study aims to define a unified threat model and to comparatively evaluate password-based, multi-factor, and passwordless authentication approaches under realistic adversary capabilities. The analysis classifies major attack vectors (online and offline guessing, credential reuse, phishing, and session takeover) and considers probabilistic models for estimating compromise success as well as compositional principles for combining factors. For password-based schemes, we show that attack success probability depends on the effective password search space, the computational cost of verifying guesses, and attempt-limiting controls. For multi-factor authentication, improved robustness is explained by a multiplicative decrease in compromise probability under factor independence. For passwordless approaches, we describe public-key challenge–response protocols that increase phishing resistance and reduce credential reuse risks. Finally, we provide practical recommendations on selecting authenticators by risk level, enforcing strict attempt limiting, enabling device binding, and applying context-aware risk assessment. The presented results can serve as a methodological basis for designing and experimentally validating strengthened authentication solutions.